Fluorine-containing polymer insulating material for cable as well as preparation method and application of fluorine-containing polymer insulating material

The novel fluoropolymer insulation material addresses thermal stability and crosslinking inefficiencies by using N-Allyl Benzamide and Diallyl Isocyanurate, along with Sb2O3 and MgO, to enhance electrical insulation, resistance to aging, and electromagnetic shielding in cable applications.

CN120310164AActive Publication Date: 2025-07-15GUANGZHOU PANYU CABLE WORKS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510451972.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-11
Publication Date
2025-07-15
Estimated Expiration
2045-04-11

AI Technical Summary

Technical Problem

The existing fluoropolymer cross-linking sensitizers have problems such as poor thermal stability, low self-polymerization temperature and insufficient cross-linking activity, resulting in a degradation of the performance of cable insulation materials.

Method used

N-allylbenzamide and diallyl isocyanurate are used as a combination of sensitizers, combined with Sb2O3 and MgO as acid absorbents, and optimize the crosslinking environment by precisely controlling their proportion and particle size, improving crosslinking efficiency and material performance.

Benefits of technology

It significantly improves the electromagnetic shielding performance, aging resistance and insulation performance of fluoropolymer insulating materials, and improves the overall performance of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a fluorine-containing polymer insulating material for a cable as well as a preparation method and application of the fluorine-containing polymer insulating material. The insulating material comprises the following raw material components in parts by weight: 100 parts of fluororesin, 2-8 parts of an acid acceptor, 3-10 parts of a sensitizer, 2-5 parts of a vinyl silane coupling agent, 1-5 parts of an antioxidant, 1-5 parts of a lubricant and 5-10 parts of color master batch. Wherein the acid acceptor is prepared from Sb2O3 and MgO; and the sensitizing agent is prepared from N-allyl benzamide and diallyl isocyanurate. Through compounding of the sensitizing agent and the acid absorbing agent, a more efficient acid absorbing effect is achieved, a cross-linking environment is optimized, meanwhile, due to the high melting point and the low volatility of the sensitizing agent, the sensitizing agent can bear high processing temperature, and the defects of a traditional sensitizing agent in the aspects of self-polymerization, heat stability and high-temperature volatility are effectively overcome. On the basis, the cross-linking efficiency of the fluororesin material is remarkably improved, and the insulativity, aging resistance and electromagnetic shielding performance of the cable insulating material are further enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of cables, and more specifically, relates to a fluoropolymer insulating material for cables, its preparation method and applications. Background Art

[0002] The cable insulation layer plays a crucial role in the cable structure. Its main function is to isolate the conductors or power lines in the cable from the external environment, thereby achieving electrical insulation and preventing current leakage. The quality and performance of the cable insulation layer are directly related to the safety and reliability of the cable. However, in the prior art, some cable insulation layer materials have the problem of insufficient anti-interference ability and are easily affected by external electromagnetic interference, which in turn leads to a decline in the quality of cable signal transmission, and even data loss or transmission interruption. In addition, some insulation layer materials have poor aging resistance and are difficult to meet the usage requirements in extreme environments.

[0003] Fluoropolymers (such as PTFE, FEP, PFA, etc.) exhibit excellent electrical insulation properties due to their extremely low dielectric constant and dielectric loss, and can maintain stable electrical characteristics within a wide temperature and frequency range. This makes them particularly suitable for high-frequency signal transmission and cable insulation in high-voltage environments. These materials also possess excellent heat resistance. For example, the service temperature range of PTFE can reach from -180°C to 260°C, while materials such as FEP and PFA can also work stably for a long time at temperatures above 200°C, which makes fluoropolymer-insulated cables an ideal choice for high-temperature application scenarios such as aerospace and automotive. In addition, fluoropolymers also have high tensile strength and creep resistance, while maintaining good flexibility. Taking PVDF as an example, it not only has strong corrosion resistance, but also has high mechanical strength and wear resistance. These materials also have excellent weather resistance and ultraviolet resistance, and can maintain stable performance for a long time under harsh outdoor climate conditions, further expanding their application scope in the field of cable insulation.

[0004] The key to the formulation of fluoropolymer insulating materials lies in the selection of a suitable sensitizer. Sensitizers usually contain unsaturated carbon-hydrogen double bonds. During irradiation, these double bonds first form conjugated π bonds. When they collide with the macromolecular chains of fluororesin, they can transfer and transfer energy. For example, the C-H bonds and C-F bonds in the ETFE macromolecular chains can be more easily activated and undergo cross-linking reactions under the action of electron beams. However, the processing temperature of fluororesin is relatively high, generally between 220°C and 340°C, and common sensitizers tend to self-polymerize or decompose within this temperature range. Therefore, an ideal sensitizer needs to meet the following requirements: ① having a relatively high self-polymerization temperature; ② low volatility and volatility rate; ③ good thermal stability; ④ radiation resistance and good radiation cross-linking activity; ⑤ good compatibility with ETFE. Currently, commonly used sensitizers such as triallyl cyanurate (TAC) and triallyl isocyanate (TA-IC) have low self-polymerization temperature, high volatility, low cross-linking efficiency, and produce a large amount of smoke during processing, with a pungent smell and serious pollution.

[0005] To solve the above problems, the present invention adopts a novel sensitizer system, which is composed of an allyl sensitizer containing a benzene ring structure and diallyl isocyanurate with high cross-linking activity. This combination not only ensures that the sensitizer has a high melting point and low volatility, enabling it to withstand a relatively high processing temperature, but also effectively solves the deficiencies of traditional sensitizers in terms of self-polymerization, thermal stability, and high-temperature volatility. In addition, this novel sensitizer system further improves the thermal stability and mechanical properties of fluoropolymer insulating materials. Summary of the Invention

[0006] The present invention aims to solve the problems of poor thermal stability, low self-polymerization temperature, and insufficient cross-linking activity existing in existing cross-linking sensitizers for fluoropolymers, which lead to a decline in the performance of cable insulating materials. For this purpose, the present invention provides a fluoropolymer insulating material for cables and its preparation method, which significantly improves the electromagnetic shielding performance, aging resistance, and insulation performance of fluoropolymer insulating cable materials.

[0007] The present invention provides a fluoropolymer insulating material for cables, which includes the following raw material components in parts by weight: 100 parts of fluororesin, 2-8 parts of acid absorbent, 3-10 parts of sensitizer, 2-5 parts of vinyl silane coupling agent, 1-5 parts of antioxidant, 1-5 parts of lubricant, and 5-10 parts of masterbatch.

[0008] Preferably, the acid absorbent includes Sb2O3 and MgO, and the weight ratio of Sb2O3 to MgO is 2-6:1-4.

[0009] Preferably, the average particle size (D50) of Sb2O3 is 10-30μm, and the average particle size (D50) of MgO is 0.5-5μm.

[0010] Preferably, the sensitizer includes N-allyl benzamide and diallyl isocyanurate, and the weight ratio of N-allyl benzamide to diallyl isocyanurate is 4-10:1-3.

[0011] Preferably, the fluororesin includes at least one of polytetrafluoroethylene, polyethylene-tetrafluoroethylene, perfluoroethylene-propylene copolymer, polyvinylidene fluoride, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, and polychlorotrifluoroethylene.

[0012] Preferably, the vinyl silane coupling agent includes at least one of vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltris(β-methoxyethoxy)silane.

[0013] Preferably, the antioxidant includes at least one of antioxidant DLTDP, antioxidant 1010, antioxidant 1076, antioxidant B277, antioxidant 1790, antioxidant 168, and antioxidant DSTDP.

[0014] Preferably, the lubricant includes at least one of polyethylene wax, pentaerythritol stearate, magnesium stearate, calcium stearate, and silicone.

[0015] Preferably, the color masterbatch is at least one of carbon black masterbatch and titanium dioxide masterbatch.

[0016] The present invention uses N-allyl benzamide (N-Allyl Benzamide) and diallyl isocyanurate (Diallyl Isocyanurate, abbreviated as DAIC) as a sensitizer combination for radiation crosslinking, which has the effect of synergistically promoting crosslinking. Due to the combination of the benzene ring and the allyl group in N-allyl benzamide, it exhibits excellent thermal stability and radiation sensitivity. It has a stable benzene ring structure and can maintain stability during high-temperature processing. Even above 200 °C, it can maintain good thermal stability and will not decompose easily. And DAIC, as an effective radiation crosslinking sensitizer, during the radiation process, the double bonds in its molecular structure can absorb radiation energy, trigger free radical reactions, and promote the crosslinking of fluororesin. The crosslinked network structure formed in the fluoropolymer significantly improves the thermal stability, mechanical properties, and chemical resistance of the cable insulation material. In addition, DAIC can also act as a plasticizer during processing to optimize the processing performance of the fluoropolymer. By combining the use of N-allyl benzamide and DAIC, the present invention not only solves the problems of conventional sensitizers in terms of self-polymerization, thermal stability, and high-temperature volatilization, but also further improves the thermal stability and mechanical properties of the fluoropolymer insulation material.

[0017] In the present invention, with the increase in the content of the sensitizer, the number of free radicals generated by its decomposition will increase rapidly, which promotes more fluororesin molecules to participate in the cross-linking reaction, increases the entanglement and cross-linking opportunities between molecular chains, and thus rapidly improves the cross-linking degree. However, when the content of the sensitizer reaches a certain critical value, the growth of the cross-linking degree will gradually level off and may even decrease. This is because when the sensitizer is in excess, the molecular chains inside the insulating material will change from a one-dimensional linear structure to a three-dimensional network structure, which will hinder the free movement of other cross-linked fluororesin molecules, thereby reducing the cross-linking efficiency and resulting in a decline in the comprehensive performance of the insulating material. On the contrary, if the content of the cross-linking agent is insufficient, it will also lead to a reduction in the cross-linking efficiency, thereby affecting the performance of the insulating material. Therefore, reasonable control of the content of the sensitizer is crucial for optimizing the cross-linking effect and improving the performance of the insulating material.

[0018] In the present invention, when the weight ratio of N-allylbenzamide to diallyl isocyanurate is controlled within 4 - 10:1 - 3, the two can significantly synergistically promote cross-linking. However, if the compounding ratio is too high, the effect of improving the cross-linking degree of the insulating material will gradually weaken; if the ratio is too low, it will lead to insufficient cross-linking efficiency of the fluorinated insulating material, thereby affecting the overall performance of the cable. Therefore, by precisely controlling the content of the cross-linking agent in the raw materials and optimizing the weight ratio of the compounded cross-linking agent, the present invention can effectively improve the cross-linking degree of the fluororesin, thereby endowing the cable insulating compound with excellent cross-linking performance and good mechanical properties and other performances.

[0019] The present invention uses a combination of Sb2O3 (antimony trioxide) and MgO (magnesium oxide) as an acid absorbent to neutralize the acidic by-products (such as hydrofluoric acid, HF) generated in the cross-linking reaction, thereby protecting the material performance. Among them, Sb2O3 can quickly neutralize HF, reduce the corrosion of the material by acidic substances, and still maintain good acid absorption performance under high-temperature conditions. At the same time, it can also improve the flame retardant performance of the material. And MgO, due to its high density of basic sites, can quickly react chemically with acidic substances to absorb the acidic substances generated during the cross-linking process. In addition, MgO usually has a developed porous structure and a large specific surface area, which can provide more adsorption sites and significantly improve the acid absorption efficiency. During the cross-linking process of the fluororesin, Sb2O3 and MgO effectively improve the cross-linking environment by neutralizing acidic substances, and improve the cross-linking efficiency and stability. Sb2O3 is suitable for high-temperature environments, while MgO performs excellently with its high acid absorption capacity and good dispersibility. When the two are used in combination, the cross-linking effect can be further optimized. In the present invention, by precisely controlling the weight ratio of Sb2O3 to MgO, HF can be quickly neutralized, the cross-linking environment can be effectively improved, and thus the performance of the cable insulating layer can be significantly improved.

[0020] In the present invention, the inventors further found through research that preferably, the average particle size (D50) of Sb2O3 is 10 - 30 μm, while the average particle size (D50) of MgO is 0.5 - 5 μm. Sb2O3 has a larger particle size and can form a macroscopic acid absorption protective layer in the material, quickly neutralizing acidic by-products (such as HF) generated during the cross-linking process and reducing its corrosion of the material. At the same time, MgO has a smaller particle size, a higher specific surface area, and a porous structure, which can penetrate deep into the material, provide more adsorption sites, quickly absorb local acidic substances, and achieve a more uniform acid absorption effect. Due to the particle size difference between Sb2O3 and MgO, a multi-level dispersion structure is formed in the material, effectively avoiding the local accumulation of acidic substances during the cross-linking process, thereby achieving a more efficient acid absorption effect, optimizing the cross-linking environment, significantly improving the cross-linking efficiency, mechanical properties, and thermal stability of the fluororesin material, and further greatly enhancing the overall performance of the cable insulation layer.

[0021] In the present invention, the acid absorbents (Sb2O3 and MgO) used are both inorganic materials, and they are prone to agglomeration during the extrusion process, which affects the acid absorption effect and increases the processing difficulty of the material. To solve this problem, the present invention uses a vinyl silane coupling agent to modify the surface of the acid absorbent. The structure of vinyl siloxane contains vinyl functional groups, and these functional groups can form good chemical bonding with fluororesin. At the same time, its alkoxy groups (such as methoxy, ethoxy) can react with the hydroxyl groups on the surface of the acid absorbent to form strong chemical bonds. This dual action mechanism significantly improves the dispersion of the acid absorbent in the fluororesin matrix, effectively reduces the agglomeration phenomenon of the acid absorbent, thereby reducing the processing difficulty of the material and optimizing the acid absorption effect at the same time.

[0022] Furthermore, the present invention also provides a method for preparing a fluoropolymer insulating material for cables, comprising the following steps:

[0023] Mix the components evenly in proportion, melt-blend in an extruder, and irradiate for cross-linking to obtain the fluoropolymer insulating material.

[0024] Preferably, the screw speed of the extruder is 30 - 40 revolutions per minute, and the temperature is 180°C - 280°C; the irradiation cross-linking uses an irradiation dose of 5 - 50 Mrad and an irradiation time of 5 - 20 min.

[0025] The present invention also provides a shielded cable with insulation and aging resistance, which sequentially includes a conductor layer, a cable insulation layer, and a cable sheath layer from inside to outside, wherein the cable insulation layer is prepared from the fluoropolymer insulating material.

[0026] Furthermore, the present invention also provides the application of the above cable in the field of aerospace vehicles.

[0027] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0028] The fluoropolymer insulating material for cables described in the present invention has excellent insulation, aging resistance and electromagnetic shielding performance. By compounding a sensitizer and an acid absorbent, a more efficient acid absorption effect is achieved, the crosslinking environment is optimized, and the crosslinking efficiency of the fluororesin material is significantly improved, further enhancing the insulation, aging resistance and electromagnetic shielding performance of the cable insulating material. Detailed implementation manners

[0029] To better illustrate the purpose, technical solution and advantages of the present invention, the technical solution of the present invention will be further described below in conjunction with specific implementation manners. However, the following examples are only simple examples of the present invention and do not represent or limit the scope of the claimed protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0030] The materials, reagents, etc. used in the following examples are commercially available reagents and materials unless otherwise specified. Example 1

[0031] This example discloses a fluoropolymer insulating material for cables, which includes 100 parts of fluororesin, 2 parts of acid absorbent, 4 parts of sensitizer, 2 parts of vinylsilane coupling agent, 3 parts of antioxidant, 5 parts of lubricant, and 5 parts of masterbatch.

[0032] The acid absorbent includes Sb2O3 and MgO, and the weight ratio of Sb2O3 to MgO is 2:1. The average particle size (D50) of Sb2O3 is 10 μm, and the average particle size (D50) of MgO is 0.5 μm.

[0033] The sensitizer includes N-allylbenzamide and diallylisocyanuric acid ester, and the weight ratio of N-allylbenzamide to diallylisocyanuric acid ester is 4:1.

[0034] The fluororesin is polytetrafluoroethylene, the vinylsilane coupling agent includes vinyltrimethoxysilane; the antioxidant is a combination of antioxidant 1010 and antioxidant 168 in a ratio of 2:1. The lubricant is a combination of polyethylene wax and pentaerythritol stearate in a ratio of 1:1.

[0035] This example also discloses a preparation method of a fluoropolymer insulating material for cables, which specifically includes the following steps:

[0036] Dry polytetrafluoroethylene at 80 °C for 5 hours, blend polytetrafluoroethylene, acid absorbent, sensitizer, vinylsilane coupling agent, antioxidant, lubricant, and masterbatch according to the mass ratio, melt extrude in an extruder, pelletize, dry, press into a standard sheet sample with a tablet press, then irradiate the sample with electrons, and finally let the sample stand at room temperature for 7 days, then make a sample and conduct performance tests.

[0037] Among them, the screw speed of the extruder is 30 revolutions per minute, and the extrusion temperature is 250 °C; the tablet pressing temperature is 280 °C, the irradiation intensity is 10 Mrad, and the irradiation time is 10 min. Example 2

[0038] This example discloses a fluoropolymer insulating material for cables, including 100 parts of fluororesin, 8 parts of acid absorbent, 7 parts of sensitizer, 5 parts of vinyl silane coupling agent, 5 parts of antioxidant, 2 parts of lubricant, and 8 parts of masterbatch.

[0039] The acid absorbent includes Sb2O3 and MgO, and the weight ratio of Sb2O3 to MgO is 6:1. The average particle size (D50) of Sb2O3 is 30 μm, and the average particle size (D50) of MgO is 4 μm.

[0040] The sensitizer includes N-allylbenzamide and diallyl isocyanurate, and the weight ratio of N-allylbenzamide to diallyl isocyanurate is 10:1.

[0041] The fluororesin is polyethylene-tetrafluoroethylene, the vinyl silane coupling agent includes vinyltriethoxysilane; the antioxidant is a combination of antioxidant DLTDP and antioxidant 168 in a ratio of 3:1. The lubricant is a combination of polyethylene wax and silicone in a ratio of 2:1.

[0042] This example also discloses a preparation method of a fluoropolymer insulating material for cables, specifically including the following steps:

[0043] Dry the polyethylene-tetrafluoroethylene at 80 °C for 5 hours, blend the polyethylene-tetrafluoroethylene, acid absorbent, sensitizer, vinyl silane coupling agent, antioxidant, lubricant, and masterbatch according to the mass ratio, melt and extrude in an extruder, granulate, dry, press into a standard sheet sample with a tablet press, then irradiate the sample with electrons, and finally place the sample at room temperature and let it stand for 7 days, and then make a sample and conduct performance tests.

[0044] Among them, the screw speed of the extruder is 35 revolutions per minute, and the extrusion temperature is 210 °C; the tablet pressing temperature is 270 °C, the irradiation intensity is 40 Mrad, and the irradiation time is 8 min. Example 3

[0045] This example discloses a fluoropolymer insulating material for cables, including 100 parts of fluororesin, 4 parts of acid absorbent, 10 parts of sensitizer, 4 parts of vinyl silane coupling agent, 5 parts of antioxidant, 3 parts of lubricant, and 10 parts of masterbatch.

[0046] The acid absorbent includes Sb2O3 and MgO, and the weight ratio of Sb2O3 to MgO is 1:2. The average particle size (D50) of Sb2O3 is 25 μm, and the average particle size (D50) of MgO is 3 μm.

[0047] The sensitizer includes N-allylbenzamide and diallyl isocyanurate, and the weight ratio of N-allylbenzamide to diallyl isocyanurate is 4:3.

[0048] The fluororesin is perfluoroethylene propylene, the vinyl silane coupling agent includes vinyl tris(β-methoxyethoxy)silane; the antioxidant is a combination of antioxidant 1010 and antioxidant 168 in a ratio of 3:1. The lubricant is a combination of calcium stearate and silicone in a ratio of 2:1.

[0049] This example also discloses a preparation method of a fluoropolymer insulating material for cables, which specifically includes the following steps:

[0050] Dry the perfluoroethylene propylene at 80 °C for 5 hours, blend the perfluoroethylene propylene, acid absorbent, sensitizer, vinyl silane coupling agent, antioxidant, lubricant, and color masterbatch according to the mass ratio, melt and extrude in an extruder, pelletize, dry, press into a standard sheet sample with a tablet press, then irradiate the sample with electrons, and finally place the sample at room temperature and let it stand for 7 days, and then make a sample and conduct performance tests.

[0051] Among them, the screw speed of the extruder is 40 revolutions per minute, and the extrusion temperature is 280 °C; the tableting temperature is 280 °C, the irradiation intensity is 50 Mrad, and the irradiation time is 5 min. Example 4

[0052] This example discloses a fluoropolymer insulating material for cables, including 100 parts of fluororesin, 5 parts of acid absorbent, 7 parts of sensitizer, 2 parts of vinyl silane coupling agent, 5 parts of antioxidant, 3 parts of lubricant, and 10 parts of color masterbatch.

[0053] The acid absorbent includes Sb2O3 and MgO, and the weight ratio of Sb2O3 to MgO is 3:2. The average particle size (D50) of Sb2O3 is 15 μm, and the average particle size (D50) of MgO is 1 μm.

[0054] The sensitizer includes N-allylbenzamide and diallyl isocyanurate, and the weight ratio of N-allylbenzamide to diallyl isocyanurate is 10:3.

[0055] The fluororesin is polyvinylidene fluoride, the vinyl silane coupling agent includes vinyl triethoxysilane; the antioxidant is a combination of antioxidant 1010 and antioxidant DSTDP in a ratio of 2:1. The lubricant is a combination of calcium stearate and silicone in a ratio of 2:1.

[0056] This embodiment also discloses a preparation method of a fluoropolymer insulating material for cables, which specifically includes the following steps:

[0057] Dry polyvinylidene fluoride at 80 °C for 5 hours, blend polyvinylidene fluoride, acid absorbent, sensitizer, vinylsilane coupling agent, antioxidant, lubricant, and masterbatch according to the mass ratio, melt-extrude in an extruder, pelletize, dry, press into a standard sheet sample with a tablet press, then irradiate the sample with electrons, and finally let the sample stand at room temperature for 7 days, and then prepare the sample and conduct performance tests.

[0058] Among them, the screw speed of the extruder is 40 revolutions per minute, and the extrusion temperature is 180 °C; the tablet pressing temperature is 200 °C, the irradiation intensity is 5 Mrad, and the irradiation time is 20 min. Example 5

[0059] This embodiment discloses a fluoropolymer insulating material for cables, which includes 100 parts of fluororesin, 6 parts of acid absorbent, 3 parts of sensitizer, 3 parts of vinylsilane coupling agent, 4 parts of antioxidant, 3 parts of lubricant, and 7 parts of masterbatch.

[0060] The acid absorbent includes Sb2O3 and MgO, and the weight ratio of Sb2O3 to MgO is 2:3. The average particle size (D50) of Sb2O3 is 30 μm, and the average particle size (D50) of MgO is 4 μm.

[0061] The sensitizer includes N-allylbenzamide and diallyl isocyanurate, and the weight ratio of N-allylbenzamide to diallyl isocyanurate is 7:3.

[0062] The fluororesin is tetrafluoroethylene-perfluoroalkyl vinyl ether, the vinylsilane coupling agent includes vinyltriethoxysilane; the antioxidant is a combination of antioxidant 1010 and antioxidant B277 in a ratio of 3:1. The lubricant is a combination of calcium stearate and silicone in a ratio of 2:1.

[0063] This embodiment also discloses a preparation method of a fluoropolymer insulating material for cables, which specifically includes the following steps:

[0064] Dry tetrafluoroethylene-perfluoroalkyl vinyl ether at 80 °C for 5 hours, blend tetrafluoroethylene-perfluoroalkyl vinyl ether, acid absorbent, sensitizer, vinylsilane coupling agent, antioxidant, lubricant, and masterbatch according to the mass ratio, melt-extrude in an extruder, pelletize, dry, press into a standard sheet sample with a tablet press, then irradiate the sample with electrons, and finally let the sample stand at room temperature for 7 days, and then prepare the sample and conduct performance tests.

[0065] Among them, the screw speed of the extruder is 40 revolutions per minute, and the extrusion temperature is 210 °C; the tablet pressing temperature is 240 °C, the irradiation intensity is 35 Mrad, and the irradiation time is 6 min. Example 6

[0066] This example discloses a fluoropolymer insulating material for cables, which includes 100 parts of fluororesin, 7 parts of acid absorbent, 6 parts of sensitizer, 5 parts of vinyl silane coupling agent, 5 parts of antioxidant, 3 parts of lubricant, and 8 parts of masterbatch.

[0067] The acid absorbent includes Sb2O3 and MgO, and the weight ratio of Sb2O3 to MgO is 2:3. The average particle size (D50) of Sb2O3 is 20 μm, and the average particle size (D50) of MgO is 3 μm.

[0068] The sensitizer includes N-allylbenzamide and diallyl isocyanurate, and the weight ratio of N-allylbenzamide to diallyl isocyanurate is 6:3.

[0069] The fluororesin is polychlorotrifluoroethylene, and the vinyl silane coupling agent includes vinyltriethoxysilane; the antioxidant is a combination of antioxidant 1010 and antioxidant 1790 in a ratio of 1:1. The lubricant is a combination of magnesium stearate and silicone in a ratio of 2:1.

[0070] This example also discloses a preparation method of a fluoropolymer insulating material for cables, which specifically includes the following steps:

[0071] Dry the polychlorotrifluoroethylene at 80 °C for 5 hours, blend the polychlorotrifluoroethylene, acid absorbent, sensitizer, vinyl silane coupling agent, antioxidant, lubricant, and masterbatch according to the mass ratio, melt and extrude in an extruder, granulate, dry, press into a standard sheet sample with a tablet press, then irradiate the sample with electrons, and finally place the sample at room temperature and let it stand for 7 days, and then make a sample and conduct performance tests.

[0072] Among them, the screw speed of the extruder is 45 revolutions per minute, and the extrusion temperature is 210 °C; the tablet pressing temperature is 210 °C, the irradiation intensity is 25 Mrad, and the irradiation time is 8 min. Example 7

[0073] The difference from Example 2 is that: the average particle size (D50) of the Sb2O3 is 5 μm, and the average particle size (D50) of the MgO is 5 μm, and other conditions are the same as those in Example 2. Example 8

[0074] The difference from Example 2 is that: the average particle size (D50) of the Sb2O3 is 30 μm, and the average particle size (D50) of the MgO is 25 μm, and other conditions are the same as those in Example 2.

[0075] Comparative Example 1

[0076] The difference from Example 2 is that the same amount of Sb2O3 is used to replace MgO, and other conditions are the same as those in Example 2.

[0077] Comparative Example 2

[0078] The difference from Example 2 is that the same amount of MgO is used to replace Sb2O3, and other conditions are the same as those in Example 2.

[0079] Comparative Example 3

[0080] The difference from Example 2 is that the same amount of N-allylbenzamide is used to replace diallyl isocyanurate, and other conditions are the same as those in Example 2.

[0081] Comparative Example 4

[0082] The difference from Example 2 is that the same amount of diallyl isocyanurate is used to replace N-allylbenzamide, and other conditions are the same as those in Example 2.

[0083] Comparative Example 5

[0084] The difference from Example 2 is that the dosage of the sensitizer is 0.5 parts, and other conditions are the same as those in Example 2.

[0085] Comparative Example 6

[0086] The difference from Example 2 is that the dosage of the sensitizer is 12 parts, and other conditions are the same as those in Example 2.

[0087] Comparative Example 7

[0088] The difference from Example 2 is that the weight ratio of N-allylbenzamide to diallyl isocyanurate is 1:3, and other conditions are the same as those in Example 2.

[0089] Comparative Example 8

[0090] The difference from Example 2 is that the weight ratio of N-allylbenzamide to diallyl isocyanurate is 13:1, and other conditions are the same as those in Example 2.

[0091] Comparative Example 9

[0092] The difference from Example 2 is that γ-aminopropyltriethoxysilane is used to replace vinyltriethoxysilane, and other conditions are the same as those in Example 2.

[0093] Performance Test

[0094] The fluoropolymer insulating materials for cables prepared in the examples and comparative examples were subjected to relevant performance tests. The specific test methods are as follows:

[0095] 1. The volume resistivity test refers to the standard "GB / T 1410-2006 Test Methods for Volume Resistivity and Surface Resistivity of Solid Insulating Materials".

[0096] 2. For the aging resistance performance test, the prepared specimens are subjected to aging treatment at 200 °C for 240 h, and the tensile strength and elongation at break before and after the test are measured respectively. The ratio of the test value after aging to the test value before aging is the retention rate of the tensile strength and elongation at break.

[0097] 3. For the electromagnetic shielding performance test, the shielding effectiveness of the obtained materials is tested according to GB / T 30142-2013. Each group of specimens is tested 5 times, and the arithmetic mean of the test results is taken.

[0098] The test results are shown in Table 1:

[0099] Table 1

[0100]

[0101] It can be seen from Examples 1-8 in Table 1 that by controlling the compounding ratio of N-allylbenzamide and diallyl isocyanurate within the range defined in the present invention, the crosslinking efficiency of the fluororesin can be significantly improved, so that the cable insulating material exhibits excellent insulation, aging resistance and electromagnetic shielding performance. In addition, by controlling the content of the sensitizer in the raw materials and the composition of the acid absorbent, the insulation, aging resistance and electromagnetic shielding performance of the cable insulating material are further optimized. By comparing Example 2 with Examples 7-8, it can be seen that the present invention further preferably selects the particle size difference between Sb2O3 and MgO to form a multi-level dispersion structure in the material. This structure effectively avoids the local accumulation of acidic substances during the crosslinking process, realizes a more efficient acid absorption effect, optimizes the crosslinking environment, significantly improves the crosslinking efficiency of the fluororesin material, and further enhances the insulation, aging resistance and electromagnetic shielding performance of the cable insulating material.

[0102] It can be seen from the comparison between Comparative Examples 1-2 and Example 2 that only one of the acid absorbents, Sb2O3 or MgO, is used in Comparative Examples 1-2, and HF generated during the crosslinking process of the fluororesin cannot be quickly neutralized, thus deteriorating the crosslinking environment and resulting in a decrease in the crosslinking efficiency of the fluororesin, which causes a decrease in the insulation performance, aging resistance and electromagnetic shielding performance of the insulating material.

[0103] It can be seen from the comparison between Comparative Examples 3-8 and Example 2 that in Comparative Examples 3-4, only one sensitizer of N-allylbenzamide or diallyl isocyanurate was used, and the synergistic effect could not be achieved, resulting in low cross-linking efficiency of the fluororesin; in Comparative Example 5, the amount of the sensitizer was insufficient, the cross-linking reaction was incomplete, and the cross-linking efficiency decreased; in Comparative Example 6, the amount of the sensitizer was too large, and the internal molecular chains of the insulating material changed from a one-dimensional linear structure to a three-dimensional network structure, which hindered the free movement of other fluororesin molecules and reduced the cross-linking efficiency, thereby resulting in a decline in the comprehensive performance of the insulating material; in Comparative Examples 7-8, the compounding ratio of N-allylbenzamide and diallyl isocyanurate exceeded the scope of this application, and the synergistic cross-linking effect could not be exerted. Finally, the insulation, aging resistance, and electromagnetic shielding performance of Comparative Examples 3-8 were all inferior to those of Example 2.

[0104] It can be seen from the comparison between Comparative Example 9 and Example 2 that in Comparative Example 9, γ-aminopropyltriethoxysilane without vinyl was used to replace vinyltriethoxysilane. Its lack of vinyl could not form a good chemical bond with the fluororesin, which led to the fact that γ-aminopropyltriethoxysilane loaded with inorganic acid absorbents (Sb2O3 and MgO) could not effectively contact the fluororesin and could not quickly neutralize the HF generated during the reaction. Finally, the cross-linking efficiency of the fluororesin-containing was reduced, and further, the insulation, aging resistance, and electromagnetic shielding performance of the insulating material all decreased significantly.

[0105] In the description of this specification, the descriptions referring to terms such as "one embodiment", "some embodiments", "example", "specific example", or "some examples" mean that the specific features, structures, materials, or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of this application. Moreover, the specific features, structures, materials, or characteristics described can be combined in a suitable manner in any one or more embodiments or examples. In addition, without contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples.

[0106] In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly specifying the quantity of the indicated technical features. Thus, the features defined with "first" and "second" can explicitly or implicitly include at least one of these features. In the description of this application, "a plurality of" means two or more unless otherwise specifically defined.

[0107] As described above, it is only the specific implementation manner of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present application can easily think of various changes or substitutions thereof, and these should all be covered within the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the protection scope of the claims.

Claims

1. A fluoropolymer insulating material for cables, characterized in that, It comprises the following raw material components in parts by weight: 100 parts of fluororesin, 2 - 8 parts of acid absorbent, 3 - 10 parts of sensitizer, 2 - 5 parts of vinyl silane coupling agent, 1 - 5 parts of antioxidant, 1 - 5 parts of lubricant, and 5 - 10 parts of masterbatch; The acid absorbent comprises Sb2O3 and MgO, and the weight ratio of Sb2O3 to MgO is 2 - 6:1 - 4; The sensitizer comprises N - allylbenzamide and diallyl isocyanurate, and the weight ratio of N - allylbenzamide to diallyl isocyanurate is 4 - 10:1 - 3.

2. The fluoropolymer insulating material for cables according to claim 1, characterized in that, The average particle size of the Sb2O3 is 10 - 30 μm, and the average particle size of the MgO is 0.5 - 5 μm.

3. The fluoropolymer insulating material for cables according to claim 1, characterized in that, The fluororesin comprises at least one of polytetrafluoroethylene, polyethylene - tetrafluoroethylene, perfluoroethylene - propylene copolymer, polyvinylidene fluoride, tetrafluoroethylene - perfluoroalkyl vinyl ether, and polychlorotrifluoroethylene.

4. The fluoropolymer insulating material for cables according to claim 1, wherein The vinyl silane coupling agent comprises at least one of vinyltrimethoxysilane, vinyltriethoxysilane, and vinyltris(β - methoxyethoxy)silane.

5. The fluoropolymer insulating material for cables according to claim 1, wherein The antioxidant comprises at least one of antioxidant DLTDP, antioxidant 1010, antioxidant 1076, antioxidant B277, antioxidant 1790, antioxidant 168, and antioxidant DSTDP; the lubricant comprises at least one of polyethylene wax, pentaerythritol stearate, magnesium stearate, calcium stearate, and silicone.

6. A method for preparing a fluoropolymer insulating material for cables as described in any one of claims 1-5, characterized in that, It comprises the following steps: Mix the components evenly according to the parts by weight, conduct melt blending in an extruder, and perform radiation cross - linking to obtain a fluoropolymer insulating material.

7. The preparation method of the fluoropolymer insulating material for cables according to claim 6, characterized in that, The screw speed of the extruder is 30 - 40 revolutions per minute, and the melting temperature is 180°C - 280°C.

8. The preparation method of the fluoropolymer insulating material for cables according to claim 6, characterized in that, For the radiation cross - linking, the radiation dose is 5 - 50 Mrad, and the radiation time is 5 - 20 min.

9. A shielded cable with insulation and aging resistance, characterized in that, It sequentially comprises a conductor layer, a cable insulation layer, and a cable sheath layer from the inside out, wherein the cable insulation layer is prepared from the fluoropolymer insulating material according to any one of claims 1 - 5.

10. An application of the shielded cable with insulation and aging resistance as claimed in claim 9 in the field of aerospace vehicles.

Citation Information

Patent Citations

  • Crosslinking sensitizer for fluorine-containing polymer

    CN105037797A

  • Die bonding adhesive and preparation method thereof

    CN107057632A

  • Flexible cable coating material, aluminum alloy flexible cable and preparation method of aluminum alloy flexible cable

    CN110415869A

  • Preparation process of irradiation crosslinking ethylene-tetrafluoroethylene copolymer insulating material

    CN114644790A

  • Radiation Crosslinked Fluoropolymer Compositions Containing Low Level of Extractable Fluorides

    US20160379734A1